PENGARUH PENGGUNAAN MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KREATIVITAS SISWA PADA MUATAN PELAJARAN IPA KELAS V SEKOLAH DASAR - Hindicha, Yuliana; ., Maryono; Sastrawati, Eka (Jurnal Tunas Pendidikan, 2024)
This research aims to determine the effect of the project-based learning model on student creativity in science lesson content for class V elementary schools. This research was carried out in class V of SDN 13/I Muara Bulian in the 2022/2023 academic year. This research is quantitative research using quasi-experiment. The data collection technique was obtained by giving written tests about descriptions to students. Data analysis techniques use normality, homogeneity, hypothesis and t tests. The results of this research show that science learning using a project-based learning model for class V SDN 13/I Muara Bulian is more influential than using a direct learning model on student creativity outcomes. Using the project-based learning model obtained a final measurement average of 74.12 and the direct learning model obtained a final measurement average of 64.54. Based on the t-test that has been carried out, the results of tcount (2.445) and ttable (1.677) are obtained. Based on the test criteria, this shows that Ha is accepted and H0 is rejected, and there are differences in the results of the project-based learning model and the direct learning model. So it can be concluded that there is a difference in learning using a project-based learning model and a direct learning model.